Are supplements consumed by middle-distance runners evidence-based? A comparative study between level of competition and sex - Del Arco, A.; Martinez Aguirre-Betolaza, A.; Malchrowicz-Mosko, E.; Gogojewicz, A.; Castañeda-Babarro, A. (Nutrients, 2023)
Background: Middle-distance running events have special physiological requirements from a training and competition point of view. Therefore, many athletes choose to take sport supplements (SS) for different reasons. To date, few studies have been carried out that review supplementation patterns in middle-distance running. The aim of the present study is to analyze the consumption of SS in these runners with respect to their level of competition, sex and level of scientific evidence. Methods: In this descriptive cross-sectional study, data was collected from 106 middle-distance runners using a validated questionnaire. Results: Of the total sample, 85.85% responded that they consumed SS; no statistical difference was found regarding the level of competition or sex of the athletes. With respect to the level of competition, differences were observed in the total consumption of SS (p = 0.012), as well as in that of medical supplements (p = 0.005). Differences were observed between sexes in the consumption of medical supplements (p = 0.002) and group C supplements (p = 0.029). Conclusions: Higher-level athletes consume SS that have greater scientific evidence. On the other hand, although the most commonly consumed SS have evidence for the performance or health of middle-distance runners, runners should improve both their sources of information and their places of purchase.